Limited value of current and new in silico predicted oocyst-specific proteins of Toxoplasma gondii for source-attributing serology - López-Ureña, Nadia-María; Calero-Bernal, Rafael; Koudela, Bretislav; Cherchi, Simona; Possenti, Alessia; Tosini, Fabio; Klein, Sandra; San Juan-Casero, Carmen; Jara-Herrera, Silvia; Jokelainen, Pikka; Regidor-Cerrillo, Javier; Ortega-Mora, Luis-Miguel; et al. (Frontiers in Parasitology, 2023)
Toxoplasma gondii is a zoonotic parasite infecting all warm-blooded animals, including humans. The contribution of environmental contamination by T. gondii oocysts to infections is understudied. The aim of the current work was to explore T. gondii serology as a means of attributing the source of infection using a robust stepwise approach. We identified in silico thirty-two promising oocyst-specific antigens from T. gondii ´omics data, recombinantly expressed and purified them and validated whether serology based on these proteins could discriminate oocyst- from tissue cyst-driven experimental infections. For this, three well-characterized serum panels, sampled from 0 to 6 weeks post-infection, from pigs and sheep experimentally infected with T. gondii oocysts or tissue cysts, were used. Candidate proteins were initially screened by Western blot with sera from pigs or sheep, infected for different times, either with oocysts or tissue cysts, as well as non-infected animals. Only the recombinant proteins TgCCp5A and TgSR1 provoked seroconversion upon infection and appeared to discriminate between oocyst- and tissue cyst-driven infections with pig sera. They were subsequently used to develop an enzyme-linked immunosorbent assay test for pigs. Based on this assay and Western blot analyses, a lack of stage specificity and low antigenicity was observed with all pig sera. The same was true for proteins TgERP, TgSporoSAG, TgOWP1 and TgOWP8, previously described as source-attributing antigens, when analyzed using the whole panels of sera. We conclude that there is currently no antigen that allows the discrimination of T. gondii infections acquired from either oocysts or tissue cysts by serological tests. This work provides robust new knowledge that can inform further research and development toward source-attributing T. gondii serology.